Expression and correlation of Surfeit 4 gene in esophageal squamous cell carcinoma - Jun-xing Liu; Ting Lu; Yin Xia; Jun Yang; Ying-feng Jiang; Yan Zhao; Hong Yu (Holistic Integrative Oncology)
Abstract Backgroud In the previous era of functional genomics, it was widely believed that the expression levels of housekeeping genes (HKGs) remained relatively constant and were unaffected by variations in tissue type, cell development stage, cell cycle state, as well as internal and external cellular environments. With the improvement of gene microarray technology and quantitative polymerase chain reaction (qPCR) technology for expression analysis of high-throughput differential genes, changes in the expression levels of HKGs have been found in certain human cancers. The present study aimed to experimentally validate the expression of Surfeit 4 gene (SURF4), a member of HKGs, in esophageal squamous cell carcinoma (ESCC). Methods The experimental techniques employed in this study encompassed real-time fluorescence quantitative polymerase chain reaction (RT-qPCR), Western blot (WB), and immunohistochemistry (IHC) to assess the mRNA and protein expression of SURF4 in ESCC, and their clinicopathological significance was statistically analyzed. Results All three tests showed significant differences between the three groups (Kruskal–Wallis test, P < 0.05). The results of the three methods indicated a significantly higher expression of SURF4 in the tumor group compared to both the adjacent paracancerous tissue group and the normal esophageal mucosal tissue group distant from the tumor. There was no significant difference between the latter two groups. Chi-square and Rank-sum test revealed the expression of SURF4 was significant statistical correlation with tumor cell differentiation, tumor progression and Ki-67 index, as well as the survival prognosis of patients (P < 0.05). Conclusions The expression of SURF4 was up-regulated in ESCC and was associated with differentiation, proliferation, progression, and clinical prognosis of ESCC. This portended epigenetically that SURF4 may play a role in tumor progression in ESCC and could potentially serve as a novel therapeutic target.